Inconsistent Association Between the STK15 F31I Genetic Polymorphism and Breast Cancer Risk - Fletcher, Olivia; Johnson, Nichola; Palles, Claire; dos Santos Silva, Isabel; McCormack, Valerie; Whittaker, John; Ashworth, Alan; Peto, Julian (JNCI : Journal of the National Cancer Institute, 2006)
STK15 may be a low-penetrance breast cancer susceptibility gene, and several reports suggest that women who are homozygous for the polymorphic variant F31I have an increased risk of breast cancer. To evaluate this potential breast cancer allele, we genotyped 507 patients with two primary breast cancers and 875 population-based control subjects for the STK15 F31I polymorphism. All statistical tests were two-sided. The Ile/Ile homozygous genotype was not associated with an increased risk in white women of British descent. The odds ratio for developing two primary breast cancers) in Ile/Ile homozygotes was 0.63 (95% confidence interval [CI] = 0.34 to 1.13), which corresponds to an odds ratio of 0.79 (95% CI = 0.58 to 1.06) for a first primary breast cancer. A meta-analysis of this study and other published studies showed statistically significant heterogeneity in the odds ratio estimates (P<.001). This heterogeneity could reflect either population-specific linkage disequilibrium with a functional variant or artifacts such as population stratification or publication bias.